Structural equation modeling-partial least squares: Analysis of the effect of hedonic value on customer satisfaction and loyalty - Nursyirwan, Vivi Iswanti; Valentika, Nina (Desimal: Jurnal Matematika, 2021)
Testing the effect of hedonic value on loyalty, the hedonic value on satisfaction, and customer satisfaction on consumer loyalty, and investigating the effect of hedonic value on consumer loyalty with customer satisfaction as an intervening variable is the purpose of this study, with a case study on e-commerce Shopee.  The sample aims to be a method of determining the sample with a total of 100 respondents. The intended respondents are Pamulang University students, Faculty of Economics, S1 Accounting Department as well as consumers of Shopee e-commerce. The Research model used SEM-PLS Structural Equation Modeling-Partial Least Square Approach. The results of this study indicate that the hedonic value has a positive influence and also has a significant value on consumer loyalty at the real level of 10%. The results of the study also state hedonic value has a significant positive effect on consumer satisfaction, and customer satisfaction has a significant positive effect on consumer loyalty with the satisfaction of consumer as a variable of intervening with 10% level.